Por que o familiar e/ou paciente resistem à assistência domiciliar? - Cruz, Eliana Farias (2005)
The study sought to investigate the reasons for non-acceptance or resistance to private home care on the part of families and/or patients for those who are prescribed home care services. The researcher proposed an investigation whereby she sought to gain a broad knowledge of home care, especially as regards the subjectivity of the subjects, with the purpose of contributing to the adoption of measures that ensure the practical efficiency of private home care regarding the patient s evaluation process. The study was conducted at a home care company located in the city of São Paulo, Brazil, and qualitative research was selected as the methodological approach. For this, participative observation of the patient was one of the investigation strategies used throughout the data collection process, in addition to the field journal. The subjects of the study were the family caregiver responsible for the patient, the patient themselves the ones who were physically able to participate in the process, the physician in charge of the patient in the hospital, the nurses in home care practice, the company s social workers, as well as the researcher-observer. Data collection began from the first telephone contact with the family member responsible for the patient with the purpose of scheduling an evaluation, and continued through the evaluation per se, which was performed at the hospital where the patient was being treated. Only one raw data was produced: Evaluation Process Reporting , and for data analysis, the methodology used was content analysis. The research showed that home care must be understood as a cultural change in healthcare services since the hospital is still perceived as the temple of science and the ideal place to treat and cure a disease; the health plan coverage for home care differs from that for hospital stays; the identification of an active family caregiver is often difficult and the support network is limited; and the home, culturally, is seen as a private and intimate realm. Therefore, the strangeness in relation to home care within this context is understandable, since the family dynamics is dramatically modified and its reorganization occurs at all levels. Since there is a growing trend towards home care and the elderly population increases yearly, a need was found to study further the changes in the household structure where such dynamics occurs, namely, what it was like before home care was implemented, what it was like after, and what it will be like after it is completed